The Relationship Between Nutritional Status and Scabies Symptoms in the Kupang City Sports Talent School (SKO) Dormitory - Jonathan Azis Hussein Geong; Regina M. Hutasoit; Gottfrieda P. Taeng-Ob Adang; Herman P. L. Wungouw (Jurnal Biologi Tropis, 2026)
Nutritional status assessment was conducted using two approaches: Body Mass Index (BMI) measurement as a non-invasive method, and hemoglobin (Hb) level examination as an invasive method. This study aimed to determine the relationship between scabies and nutritional status measured using BMI and Hb in SKO boarding school students in Kupang City. The study was an observational analytic cross-sectional design with a simple sampling technique. The research group included 144 individuals, and the sample size was determined through simple random sampling using the Slovin formula, leading to 59 participants. The chi-square statistical test was applied in this research to examine the connection between nutritional status and the occurrence of scabies. Results will be relevant if the p-value is less than 0.05. Scabies symptoms appeared in 15 participants (25.4%), while the bivariate analysis indicated no meaningful connection between nutritional status and scabies symptoms. Nutritional status evaluated through Body Mass Index (BMI) did not demonstrate a significant link with scabies symptoms, with the chi-square result yielding a value of (p = 0.814). Most participants had a normal BMI. In addition, nutritional status assessed by hemoglobin (Hb) levels also exhibited no noteworthy correlation with scabies symptoms, with a chi-square test giving a p-value of 0.531. The majority of participants had normal Hb levels. This leads to the conclusion that nutritional status is not related to scabies symptoms.